MicroRNAs and Cardiovascular Diseases - Tsuyoshi Nishiguchi (BioMed Research International, 2015)
Coronary artery diseases (CAD) and heart failure have high mortality rate in the world, although much progress has been made in this field in last two decades. There is still a clinical need for a novel diagnostic approach and a therapeutic strategy to decrease the incidence of CAD. MicroRNAs (miRNAs) are highly conserved noncoding small RNA molecules that regulate a large fraction of the genome by binding to complementary messenger RNA sequences, resulting in posttranscriptional gene silencing. Recent studies have shown that specific miRNAs are involved in whole stage of atherosclerosis, from endothelium dysfunction to plaque rupture. These findings suggest that miRNAs are potential biomarkers in early diagnosis and therapeutic targets in CAD. In the present review, we highlight the role of miRNAs in every stage of atherosclerosis, and discuss the prospects of miRNAs in the near future.